(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This research was carried out to determine suitable source of magnesium, zinc and manganese for quality of Schefflera cv. Gold Capella, plant, using three sources (-Nano, SO4 and-EDTA) as foliar sprays, under greenhouse condition. According to results, zinc from different sources showed significant increases in growth parameters (plant height, stem diameter, leaf area, numbers of leaves, and fresh and dry weights). The tallest plants with Zn-chelated. The thickest stems were found in Mg-sulphate and Zn-sulphate treated plants. Number of leaves was significantly highest in plants treated with Zn and Nano-Mn. The largest leaf area recoded with Zn-chelated and Mg-salt. The heaviest fresh dry weights of leaves, stems and roots were with Zn and Mn. The highest root number were in Zn-salt and Mn-chelated and Nano-Mg was more effective than the other Mg-sources. All sources of Mg and Nano-Zn, increased the chlorophyll content, over Mn and control. The highest carbohydrate % was in leaves from Mn-salt treated plants, followed by Zn-chelated. Total indoles and phenolic compounds were high in all Zn-sorces followed by Mg-salt. The highest N% and P% were recorded with Nano-treatments, meanwhile, K-% was highest in Mn-chelated and Nano-Zn treatments.